Marriage Discourses Historical and Literary Perspectives on Gender Inequality and Patriarchic Exploitation - Mohammed, Jowan A.; Jacob, Frank (De Gruyter, 2021)
Marriage was historically not only a romantic ideal, but a tool of exploitation of women in many regards. Discourses about marriage in history and literature naturally became more and more heated, especially during the "long" 19th century. The present volume provides a discussion of the marriage discourses in different chronological and geographical contexts and shows which arguments played an important role in the demand for more equality.